2017
DOI: 10.1071/mf16222
|View full text |Cite
|
Sign up to set email alerts
|

Broad-scale coastal movements of white sharks off Western Australia described by passive acoustic telemetry data

Abstract: Movements of 89 acoustically tagged subadult and adult white sharks (Carcharodon carcharias) were monitored off the south and west coasts of Western Australia (WA) between December 2008 and May 2016 by a network of up to 343 passive acoustic receivers. In all, 290 inter-regional movements, totalling 185092km were recorded for 73 of these sharks. Estimated rates of movement in excess of 3kmh–1 (mean 1.7kmh–1; maximum 5.6kmh–1) were common, even over distances of thousands of kilometres. Detections indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…White sharks in the Australasian region differ genetically from other populations (Pardini et al 2000), and data suggest there are 2 populations in southern Australia separated east and west by Bass Strait (Blower et al 2012). This Australasian population structure is further supported by acoustic and satellite tagging studies (Bruce & Bradford 2012, McAuley et al 2017.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…White sharks in the Australasian region differ genetically from other populations (Pardini et al 2000), and data suggest there are 2 populations in southern Australia separated east and west by Bass Strait (Blower et al 2012). This Australasian population structure is further supported by acoustic and satellite tagging studies (Bruce & Bradford 2012, McAuley et al 2017.…”
Section: Introductionmentioning
confidence: 59%
“…These rates are consistent with other studies. McAuley et al (2017) estimated that a 1.8 m (TL) male white shark travelled at a rate of 5.6 km h −1 covering 193 km in only 35 h. A further 25 sharks were estimated to have rates of movement of over 3 km h −1 for distances between 103 and 3362 km. Domeier & Nasby-Lucas (2008) showed that adult white sharks travelled along a migration corridor offshore into the eastern Pacific at speeds of approximately 3.2 km h −1 , suggesting that rapid, direct, longdistance movements are relatively common for this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology has since seen widespread application in the real-time detection of potentially dangerous megafauna along the Australian coast, principally to help manage the risk of shark attacks along popular beaches. McAuley et al (2017) provide a recent application of this technology to understand ecological drivers of white shark (Carcharodon carcharias) movements in a public safety context. This synthesis found little evidence of predictable movement patterns across broad scales, either in the location of animals, the direction of their migration or the timing of their movements; however, the data did suggest some predictable patterns in movement at smaller, regional scales (McAuley et al 2017).…”
Section: Movement Ecology In a Management Contextmentioning
confidence: 99%
“…McAuley et al (2017) provide a recent application of this technology to understand ecological drivers of white shark (Carcharodon carcharias) movements in a public safety context. This synthesis found little evidence of predictable movement patterns across broad scales, either in the location of animals, the direction of their migration or the timing of their movements; however, the data did suggest some predictable patterns in movement at smaller, regional scales (McAuley et al 2017). The integration of this technology with both the national network and use of smartphone apps (see http://www.dpi.nsw.…”
Section: Movement Ecology In a Management Contextmentioning
confidence: 99%